Pemanfaatan Lingkungan sebagai Media Pembelajaran bagi Guru Sekolah di Desa Padang Brahrang Kabupaten Langkat - Satriadi (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2021)
The main purpose of this research is to obtain an overview of the use of the environment as a medium for learning Islamic religious education in Padang Brahrang Village. In detail, the purpose of this study is divided into the following points: First, to find out the concept of using nature as a medium for learning Islamic religious education in Padang Brahrang Village. Second, to describe the implementation of Islamic education by utilizing nature as a medium for learning Islam in Padang Brahrang Village. Third, to find out the supporting and inhibiting factors in utilizing nature as a medium for PAI learning in Padang Brahrang Village